Why Latin America Needs World-Class Universities - Altbach, Philip; Salmi, Jamil (International Higher Education, 2021)
Latin America’s research universities have underperformed, and the region has few world-class institutions. For Latin America to thrive in the twenty-first century, it needs high quality universities. We argue that this is in part because of the “Cordoba academic revolution” and its academic ideas. The great public universities in Latin America need reform.